Incisor crowding evaluation in children aged 7-11 years attending orthodontic clinics of the college of dentistry at Hawler Medical University. - Shaho Ziyad Jamil Al-Talabani (Erbil Dental Journal)
Background and Objective: This study aimed to assess the permanent incisor region's crowding in both maxillary and mandibular arches among schoolchildren in Erbil city. Method: Eighty-two dental casts of schoolchildren, aged 7 to 11 years, who attended orthodontic clinics in the dentistry college at Hawler Medical University, Erbil, Iraq, were studied by one examiner. Results: (Around 47.6% of the children had crowding in the maxillary arch, 60.97% in the mandibular arch, and 32.92% of the children had crowding in both maxillary and mandibular arches. Conclusion: It can be concluded that incisor crowding varies significantly (p <0.05) between the maxillary and mandibular arches in girls, and it also varies significantly (p <0.05) when comparing the data of boys and girls.